The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.652796
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Teacher Autonomy Support and Students' Deep Learning: The Mediating Role of Self-Efficacy and the Moderating Role of Perceived Peer Support

Abstract: The purpose of this research is to test the mediation effect of self-efficacy on college student's perception of teacher autonomy support and students' deep learning, and whether the peer support perceived by students can moderate the relationship between perceived teacher autonomy support and deep learning. A survey of 1,800 college students from a provincial undergraduate normal university in Guizhou Province in China was conducted through the revised Perceived Teacher Autonomy Support Scale, Deep Learning S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 98 publications
2
23
0
Order By: Relevance
“…students' online SRL), which indicated that the more teacher autonomy support students perceive, the higher the students' self-efficacy will be and thus the higher the level of their online SRL. Teacher autonomy support influences students' self-efficacy, which is consistent with previous related research (Duchatelet & Donche, 2019;Li et al, 2020;Wang et al, 2016;Zhao & Qin, 2021) conducted in a traditional face-to-face environment. Zhao and Qin (2021) revealed that teacher autonomy support has a significant influence on students' self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…students' online SRL), which indicated that the more teacher autonomy support students perceive, the higher the students' self-efficacy will be and thus the higher the level of their online SRL. Teacher autonomy support influences students' self-efficacy, which is consistent with previous related research (Duchatelet & Donche, 2019;Li et al, 2020;Wang et al, 2016;Zhao & Qin, 2021) conducted in a traditional face-to-face environment. Zhao and Qin (2021) revealed that teacher autonomy support has a significant influence on students' self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…Teacher autonomy support influences students' self-efficacy, which is consistent with previous related research (Duchatelet & Donche, 2019;Li et al, 2020;Wang et al, 2016;Zhao & Qin, 2021) conducted in a traditional face-to-face environment. Zhao and Qin (2021) revealed that teacher autonomy support has a significant influence on students' self-efficacy. Teacher autonomy support can satisfy students' internal motivation, which can encourage individual initiative (Gagné et al, 2003) and ultimately influence students' self-efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The 2016 Horizon Report (Higher Education Edition) states that Affective Computing (ACE) will be commonly used in the next 4–5 years ( Jain et al, 2016 ; Zhao and Qin, 2021 ). It is evident that facial expressions play a very crucial role in the way learners express their emotions.…”
Section: Introductionmentioning
confidence: 99%